Pembelajaran IPA Berbasis Lingkungan untuk Meningkatkan Kesadaran Ekologis Siswa SMP - Sulistyowati (IEC: Journal of Educational Innovation, 2026)
This study aims to examine the effectiveness of environment-based science learning in improving junior high school students’ ecological awareness. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The participants were eighth-grade students divided into an experimental class and a control class. The experimental group received environment-based science instruction integrating local environmental issues, observation activities, and project-based tasks, while the control group received conventional instruction. Data were collected through ecological awareness questionnaires, science achievement tests, and observation sheets. The results showed that the experimental class achieved a higher mean posttest score and N-Gain (0.54, moderate–high category) compared to the control class (0.24, low–moderate category). Statistical analysis using an independent sample t-test indicated a significant difference between the two groups (p < 0.05). The findings suggest that environment-based science learning effectively enhances students’ environmental knowledge, attitudes, and pro-environmental behaviors. Therefore, it can be recommended as an innovative and contextual strategy in science education.